2017
DOI: 10.3892/ijmm.2017.3272
|View full text |Cite
|
Sign up to set email alerts
|

Role of the cofilin 2 gene in regulating the myosin heavy chain genes in mouse myoblast C2C12 cells

Abstract: The cofilin 2 (CFL2) and myosin heavy chain (MyHC) genes play a key role in muscle development and myofibrillar formation. The aim of the present study was to investigate the effect of CFL2 on genes involved in fiber formation and the mechanisms underlying this process. Undifferentiated and differentiated C2C12 cells (UDT and DT, respectively) were transfected with CFL2 small interfering RNA (siRNA). CFL2 mRNA and protein levels were assessed using reverse transcription polymerase chain reaction (RT-PCR) and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…CFL2 localized between Z-discs in myofibrils, which affected cell proliferation, apoptosis, migration, and invasion by regulating actin filaments [51]. In addition, the expression of four MyHC isoforms in undifferentiated myoblast cells with CFL2 RNAi was found to be significantly decreased compared with that in differentiated myoblast cells [52]. Our result indicated that the down-regulated expression of miR-192 may be involved in the regulation of MyHC via the up-regulated expression of CFL2.…”
Section: Discussionmentioning
confidence: 67%
“…CFL2 localized between Z-discs in myofibrils, which affected cell proliferation, apoptosis, migration, and invasion by regulating actin filaments [51]. In addition, the expression of four MyHC isoforms in undifferentiated myoblast cells with CFL2 RNAi was found to be significantly decreased compared with that in differentiated myoblast cells [52]. Our result indicated that the down-regulated expression of miR-192 may be involved in the regulation of MyHC via the up-regulated expression of CFL2.…”
Section: Discussionmentioning
confidence: 67%
“…This fact may be related to the myogenic regulatory roles of the CFL2 gene in myoblasts; therefore, we intend to develop a new system for myogenic differentiation monitored by CFL2 from the perspective of molecular genetics and epigenetics. CFL2 depletion inactivated cell differentiation progression and inhibited the expressions of myogenic transcription factors, thereby eventually leading to impaired myogenic differentiation in myoblasts [ 11 , 42 ]. In light of this, we observed that decreased expression of CFL2 significantly suppressed myoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The remodeling of the actin cytoskeleton is an essential step for efficient myoblast fusion (37) and for AchR clustering at the NMJ (52,53). While vinculin, filamin-C, cofilin-2, and myotilin have been associated with myoblast fusion and differentiation (54)(55)(56)(57) and NMJ (58,59), little is known about the role of ACTN1 in muscles.…”
Section: Discussionmentioning
confidence: 99%